*Synthesis of MRE framework type molecular sieves

The synthesis of molecular sieves with the *MRE framework type using a reaction mixture with 1-ethylpyridinium cations as organic structure orientation agents addresses the challenges of inconsistent production, achieving molecular sieves with enhanced catalytic properties and structural characteristics.

JP2025510655APending Publication Date: 2025-04-15CHEVRON USA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024555123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-24
Filing Date
2023-02-15
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Current methods for synthesizing molecular sieves with the *MRE framework topology face challenges in achieving consistent and efficient production, particularly in directing the synthesis using organic structure orientation agents effectively.

Method used

A method involving the preparation of a reaction mixture containing a silicon atom source, an aluminum atom source, an organic structure orientation agent with 1-ethylpyridinium cations, an alkali metal source, a hydroxide ion source, and water, followed by subjecting the mixture to crystallization conditions to form molecular sieves with the *MRE framework type.

Benefits of technology

This method enables the synthesis of molecular sieves with the *MRE framework type, incorporating 1-ethylpyridinium cations within their pores, which exhibit attractive properties as catalysts for hydrocarbon dewaxing, demonstrating improved catalytic performance and structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510655000001_ABST
    Figure 2025510655000001_ABST
Patent Text Reader

Abstract

A method is provided for synthesizing *MRE molecular sieves using an organic structure directing agent comprising a 1-ethylpyridinium cation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to methods for preparing molecular sieves having the *MRE framework topology. [Background technology]

[0002] Molecular sieves are a commercially important class of materials having a specific chemical composition and a characteristic crystal structure with a defined pore structure revealed by a distinct X-ray diffraction (XRD) pattern.

[0003] Molecular sieves are classified by the Structure Commission of the International Zeolite Association according to the rules of the IUPAC Commission on Zeolite Nomenclature, according to which framework-type zeolites and other crystalline microporous crystalline materials whose structures have been established are assigned unique three-letter codes and are described, for example, in the "Atlas of Zeolite Framework Types" (Elsevier, Sixth Revised Edition, 2007).

[0004] *MRE framework type molecular sieves are disordered materials with one-dimensional 10-ring channels. *MRE framework type molecular sieves have demonstrated attractive properties as catalysts or catalyst components for the dewaxing of hydrocarbon feedstocks. *Examples of MRE framework type molecular sieves include COK-8, EU-2, EU-11, IZM-1, SSZ-91, ZBM-30, and ZSM-48.

[0005] *Several organic compounds have been shown to direct the synthesis of MRE framework type molecular sieves, including organic linear amine and polyamine compounds, diquaternary alkyl ammonium compounds and glycols.

[0006] In accordance with the present disclosure, it has now been found that *MRE framework type molecular sieves may be synthesized using organic structure directing agents that include 1-ethylpyridinium cations. Summary of the Invention

[0007] In one embodiment, a method for synthesizing a *MRE framework type molecular sieve is provided, the method comprising: (1) preparing a reaction mixture comprising: (a) a source of silicon atoms; (b) a source of aluminum atoms; (c) an organic structure directing agent [Q] comprising a 1-ethylpyridinium cation; (d) a source of alkali metal [M]; (e) a source of hydroxide ions; and (f) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve.

[0008] In another embodiment, there is provided a *MRE framework type molecular sieve, which in its as-synthesized form contains 1-ethylpyridinium cations within its pores. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows the powder X-ray diffraction (XRD) pattern of the as-synthesized *MRE framework-type material according to Example 1.

[0010] [Diagram 2] 1 shows a scanning electron microscope (SEM) image of the as-synthesized *MRE framework-type material according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] definition The term "framework type" is used in the sense described in "Atlas of Zeolite Framework Types", by Ch. Baerlocher, LBMcCusker, and DH Olson (Elsevier, Sixth Revised Edition, 2007).

[0012] The terms "framework type" and "framework topology" should be understood to be synonymous.

[0013] The term "as-synthesized" is used herein to refer to the molecular sieve in its form after crystallization and prior to removal of the organic structure directing agent used in the synthesis of the molecular sieve. Reaction mixture

[0014] In general, *MRE framework type molecular sieves can be synthesized by: (1) preparing a reaction mixture comprising: (a) a source of silicon atoms; (b) a source of aluminum atoms; (c) an organic structure directing agent [Q] comprising a 1-ethylpyridinium cation; (d) a source of alkali metal [M]; (e) a source of hydroxide ions; and (f) water; and (2) subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve.

[0015] The reaction mixture may have a composition, in terms of molar ratios, within the ranges shown in Table 1. [Table 1]

[0016] Examples of sources of silicon atoms include colloidal suspensions of silica, precipitated silica, fumed silica, alkali metal silicates, tetraalkylorthosilicates, and mixtures thereof.

[0017] Examples of aluminum atom sources include hydrated alumina, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, and water-soluble aluminum salts (eg, aluminum nitrate), and mixtures thereof.

[0018] Sources of combined silicon and aluminum atoms, such as aluminosilicate zeolites (e.g., Y zeolites), may also be used. Aluminosilicate zeolites may be used as the sole or primary source of both silicon and aluminum. The term "predominant" means more than 50 mol%, suitably more than 75 mol%, and preferably more than 90 mol%.

[0019] The alkali metal [M] may be selected from lithium, sodium, potassium, rubidium, cesium, or mixtures thereof. In some embodiments, the alkali metal is selected from sodium and / or potassium. The alkali metal is typically introduced into the reaction mixture together with a source of hydroxide ions.

[0020] The organic structure directing agent [Q] comprises a 1-ethylpyridinium cation represented by the following structure (1): [ka]

[0021] Suitable sources of Q are the hydroxides, chlorides, bromides, and / or other salts of quaternary ammonium compounds.

[0022] The reaction mixture may also contain seeds of crystalline material such as ZSM-48 from a previous synthesis, desirably in an amount of 0.01 to 10,000 ppm by weight (e.g., 100 to 5000 ppm by weight) of the reaction mixture. Seeding may be advantageous in reducing the time required for complete crystallization to occur. Additionally, seeding may lead to improved purity of the resulting product by promoting nucleation and / or formation of the desired molecular sieve over any undesired phases.

[0023] The reaction mixture components may be supplied by multiple sources, or two or more reaction mixture components may be provided by a single source.

[0024] The reaction mixture may be prepared by any conceivable means, preferably by stirring, The reaction mixture may be prepared in batch, continuous, or semi-continuous mode.

[0025] The reaction mixture may be in the form of a solution, a colloidal dispersion (colloidal sol), a gel, or a paste, with a gel being preferred. Crystallization and post-synthesis treatment

[0026] Crystallization of the molecular sieves from the reaction mixture may be carried out under static or stirred conditions in a suitable reaction vessel, such as, for example, a polypropylene jar or Teflon-lined or stainless steel autoclave, placed in a convection oven maintained at a temperature of 100-200° C. for a period of time sufficient for crystallization to occur (e.g., about 1 day to 21 days, or 1 day to 14 days, or 1 day to 7 days).

[0027] Once the desired molecular sieve crystals have formed, the solid product may be separated from the reaction mixture by standard mechanical separation techniques such as centrifugation or filtration. The recovered crystals are water washed and then dried for a few seconds to a few minutes (e.g., 5 seconds to 10 minutes for quick drying) or for a few hours (e.g., 4 hours to 24 hours for oven drying at 75°C to 150°C) to obtain the as-synthesized molecular sieve crystals. The drying step may be performed under vacuum or at atmospheric pressure.

[0028] As a result of the crystallization process, the recovered as-synthesized crystalline molecular sieve product contains within its pore structure at least a portion of the organic structure directing agent (e.g., 1-ethylpyridinium cation) used in the synthesis.

[0029] The organic structure directing agent can be removed by calcination, where the as-synthesized molecular sieve is heated under an oxidizing atmosphere such as air or oxygen, a neutral atmosphere such as nitrogen or other inert gas, or a reducing atmosphere such as hydrogen, which may be dry or contain water.

[0030] The temperature used in calcination depends on the components in the material being calcined, and is generally between 400°C and 900°C for about 1 to 8 hours. In some cases, calcination may be carried out at temperatures up to 1200°C. For applications involving the methods described herein, calcination is generally carried out at temperatures between 400°C and 700°C for about 1 to 8 hours, preferably between 400°C and 650°C for about 1 to 4 hours.

[0031] The molecular sieves synthesized by the methods of the invention may contain one or more extra-framework alkali metals. Typically, it is desirable to remove the alkali metal cations by ion exchange and replace them with hydrogen, ammonium, or any desired metal ion. A typical ion exchange technique involves contacting the synthesized molecular sieve with a solution containing a salt of the desired replacing cation(s). A wide variety of salts may be used, with chlorides and other halides, nitrates, sulfates, and carbonates being particularly preferred. Representative ion exchange techniques are widely known in the art. Ion exchange occurs after synthesis and may be performed either before or after calcination of the molecular sieve. After contact with the salt solution of the desired replacing cation, the molecular sieve is typically washed with water and dried at a temperature ranging from 65°C to 200°C (e.g., 80°C to 150°C). After washing, the molecular sieve can be calcined in an inert gas and / or air at a temperature ranging from 400° C. to 900° C. for a time ranging from 1 to 48 hours or more to produce a catalytically active and stable product.

[0032] Molecular sieve characterization The *MRE framework-type molecular sieve synthesized by the methods described herein can have a SiO2 / Al2O3 molar ratio (SAR) of at least 60 (e.g., 60-150, or 60-140, or 60-130, or 65-150, or 65-140, or 65-130, or 70-150, or 70-140, or 70-130).

[0033] The *MRE framework type molecular sieve may contain less than 5 wt. % (e.g., less than 4 wt. %, or less than 3 wt. %, or less than 2 wt. %, or less than 1 wt. %) of non-*MRE material. Examples of non-*MRE material may include amorphous material, undissolved FAU, kenaiite, and ZSM-50. In some embodiments, the *MRE framework type molecular sieve may be free of non-*MRE material. "Free of non-*MRE material" means that non-*MRE solid material, if present, is present in an amount that is not detectable by X-ray diffraction.

[0034] Powder X-ray diffraction patterns were determined by standard techniques. The radiation was copper K-alpha / doublet. Slight variations in the diffraction pattern values ​​in the tables or figures may also be due to variations in the organic compounds used in the preparation, and variations in the silica to alumina molar ratios between samples. Despite these slight perturbations, the basic crystal structure of the as-synthesized and calcined materials remains substantially unchanged. EXAMPLES

[0035] The following illustrative examples are intended to be non-limiting.

[0036] Example 1 0.24 g of 50% NaOH solution, 7.86 g of deionized water, 0.56 g of 1-ethylpyridinium bromide (TCI America), and 0.03 g of Reheis F-2000 hydrated alumina (53% Al2O3, 47% H2O) were mixed together in a Teflon liner. 4.00 g of LUDOX® HS-30 colloidal silica was then added to the liner. The resulting gel was stirred until homogenous. The liner was then capped and placed in a Parr steel autoclave reactor. The autoclave was then placed in an oven heated at 160° C. for 4 days. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.

[0037] Analysis of the dried product by powder XRD (Figure 1) showed that the product had the *MRE framework topology. An SEM image of the product is shown in Figure 2, which shows a uniform field of crystals.

[0038] ICP elemental analysis revealed that the SiO2 / Al2O3 molar ratio of the product was 126.06.

[0039] Example 2 0.20 g of 50% NaOH solution, 8.90 g of deionized water, 0.63 g of 1-ethylpyridinium bromide, and 0.02 g of sodium aluminum oxide (Thermo Scientific) were mixed together in a Teflon liner. 1.00 g of CAB-O-SIL® M-5 fumed silica was then added to the liner. The resulting gel was stirred until homogenous. The liner was then capped and placed in a Parr steel autoclave reactor. The autoclave was then placed in an oven heated at 160° C. for 4 days. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.

[0040] Analysis of the dried product by powder XRD and SEM showed that the product had the *MRE framework topology.

[0041] ICP elemental analysis revealed that the SiO2 / Al2O3 molar ratio of the product was 118.43.

[0042] Example 3 0.26 g of 50% NaOH solution, 11.47 g of deionized water, and 1.00 g of CBV780 Y zeolite (SAR=80) powder were mixed together in a Teflon liner. 0.91 g of 1-ethylpyridinium bromide was then added to the liner. The resulting gel was stirred until homogenous. The liner was then capped and placed in a Parr steel autoclave reactor. The autoclave was then placed in an oven heated at 150° C. for 4 days. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.

[0043] Analysis of the dried product by powder XRD and SEM showed that the product had the *MRE framework topology.

[0044] ICP elemental analysis revealed that the SiO2 / Al2O3 molar ratio of the product was 83.70.

[0045] Example 4 0.39 g of 50% NaOH solution, 11.41 g of deionized water, and 1.00 g of CBV760 Y zeolite (SAR=60) powder were mixed together in a Teflon liner. 0.91 g of 1-ethylpyridinium bromide was then added to the liner. The resulting gel was stirred until homogenous. The liner was then capped and placed in a Parr steel autoclave reactor. The autoclave was then placed in an oven heated at 160° C. for 6 days. The solid product was collected from the cooled reactor by centrifugation, washed with deionized water, and dried at 95° C.

[0046] Analysis of the dried product by powder XRD and SEM showed that the product had the *MRE framework topology.

[0047] ICP elemental analysis revealed that the SiO2 / Al2O3 molar ratio of the product was 71.72.

[0048] Example 5 Firing The product of the synthesis stage of Example 1 was calcined in a muffle furnace under a flow of air heated to 540°C at a rate of 1°C / min, held at 540°C for 5 hours, cooled, and then analyzed by powder XRD. Analysis of the dried product by powder XRD showed that the product was still stable after calcination to remove the organic structure directing agent.

[0049] Example 6 Ammonium ion exchange The calcined material of Example 5 was treated with 10 mL (per gram of molecular sieve) of 1N ammonium nitrate solution at 90° C. for 2 hours. The solution was cooled, decanted and the same process was repeated. The dried product (NH4 form) was subjected to pore volume analysis by BET method using N2 as adsorbate. The molecular sieve had a pore size of 0.07 cm 3 The pore volume in g was shown.

[0050] Example 7 Palladium Ion Exchange Palladium ion exchange was then carried out with tetraamminepalladium(II) nitrate (0.5 wt % Pd) on the ammonium-exchanged samples of Examples 1 and 2. After ion exchange, each sample was dried at 95° C. and then calcined in air at 482° C. for 3 hours to convert the tetraamminepalladium(II) nitrate to palladium oxide.

[0051] Example 8 Hydrogen conversion rate of n-hexadecane (n-C16) 0.5 g of each palladium-exchanged sample of Example 7 was loaded into the center of a 23-inch long, 0.25-inch outer diameter stainless steel reactor tube, with alundum loaded upstream of the catalyst to preheat the feed (total pressure 1200 psig; downflow hydrogen rate of 160 mL / min (measured at 1 atm and 25°C); downflow liquid feed rate of 1 mL / hr). All materials were first reduced in flowing hydrogen at about 315°C for 1 hour. Products were analyzed by on-line capillary gas chromatography (GC) once every 30 minutes. Raw data from the GC was collected by an automated data collection / processing system, and the hydrocarbon conversion was calculated from the raw data.

[0052] The catalyst was first tested at about 260° C. to determine the temperature range for the next set of measurements. The entire temperature range gives a wide range of n-hexadecane conversions with a maximum conversion just below and above 96%. At least five on-line GC injections were collected at each temperature. Conversion was defined as the amount of n-hexadecane that reacted to produce other products, including iso-nC16 isomers. Yields were expressed as the weight percent of products other than n-C16 and included iso-C16 as a yield product. The results are presented in Table 2. [Table 2]

[0053] Good catalytic performance depends on the synergy between isomerization selectivity and temperature at 96% conversion while minimizing undesirable catalytic cracking. These catalysts exhibited desirable isomerization selectivity at 96% conversion. The catalysts also exhibited highly desirable temperatures at 96% conversion while maintaining very good isomerization selectivity. Furthermore, undesirable catalytic cracking and the associated high gas production were poorly reflected in acceptable levels of C4-cracking.

Claims

1. A method for synthesizing a molecular sieve of MRE framework type comprising: (1) preparing a reaction mixture, the reaction mixture comprising: (a) a silicon atom source; (b) an aluminum atom source; and (c) an organic structure directing agent [Q] containing a 1-ethylpyridinium cation; (d) a source of alkali metal [M]; and (e) a hydroxide ion source; and (f) water; said preparing comprising: (2) exposing the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve; The method comprising:

2. 2. The method of claim 1, wherein the reaction mixture has the following composition, in terms of molar ratio: 【Table 1】

3. 2. The method of claim 1, wherein the reaction mixture has the following composition, in terms of molar ratio: 【Table 2】

4. 2. The method of claim 1, wherein the source of silicon atoms is selected from a colloidal suspension of silica, precipitated silica, fumed silica, an alkali metal silicate, a tetraalkyl orthosilicate, or a mixture thereof.

5. 2. The method of claim 1, wherein the source of aluminum atoms is selected from hydrated alumina, aluminum hydroxide, alkali metal aluminates, aluminum alkoxides, and water-soluble aluminum salts, or mixtures thereof.

6. 2. The method of claim 1, wherein the source of both the silicon atoms and the aluminum atoms is a Y zeolite.

7. 10. The method of claim 1, wherein the crystallization conditions include a temperature of from 100° C. to 200° C. and a crystallization time of from about 1 day to about 21 days.

8. *MRE framework type molecular sieve, which in its as-synthesized form contains 1-ethylpyridinium cations within its pores.

9. At least 60 SiO 2 / Al 2 O 3 9. The molecular sieve of claim 8 having a molar ratio of:

10. SiO in the range of 60 to 150 2 / Al 2 O 3 9. The molecular sieve of claim 8 having a molar ratio of: